Dramatic Construction in Quranic Text Surah Taha – A model: جبار خماط حسن (Al-Academy, 2020)
There are many varied studies that dealt with the dramatic construction, especially books and studies that addressed drama in its construction and the method of writing it, that no textbook or a general cultural content is void of tackling the dramatic text in its construction and how the dramatic action develops in it. Therefore, a question occurs to the mind about the feasibility of dealing with the dramatic construction in this time, where many contemporary studies of dramatology and its relation and the contemporary critical directions are accumulating. This question many have two realistic aspects, yet the novelty and originality that this research shows lie in addressing a refined linguistic text in its style and connotations, such as rhetoric, communication and life that the holy Quran contains, and what its surahs talk about such as the history and conditions of the bygone nations and the lessons that we derive from the previous peoples. The holy Quran, a wonderful statement in its creativity and writing, is addressed by the researcher as a dramatic text that has an internal construction in the development and management of the internal power of events in a refined dramatic construction through a developing strategy inside the research which started by the methodological framework, and the research problem and the importance of addressing this problem, in addition to the objectives that we seek, passing through the identification of the terms. Then, the research, in its first section, addresses the theoretical framework, which tackles the concept of dramatic construction and its development inside the dramatic text. The second section deals with the research procedures by adopting the descriptive analytic approach and addressing the research sample represented by the blessed surah Taha. Then we conclude the research with the results and conclusions and a list of resources.